Sensitivity of Seismic Velocity Changes to the Tidal Strain at Different Lapse Times: Data Analyses of a Small Seismic Array at Izu‐Oshima Volcano. Issue 3 (28th March 2019) - Takano, Tomoya; Nishimura, Takeshi; Nakahara, Hisashi; Ueda, Hideki; Fujita, Eisuke
Abstract: We investigate seismic velocity changes in response to the tidal strain at Izu‐Oshima volcano, Japan, by analyzing the data of permanent seismic stations and a small seismic array to evaluate the characteristics of strain sensitivity of velocity changes. We estimate the seismic velocity changes by phase differences between cross‐correlations functions of ambient noises at the frequency of 2–4 Hz stacked for time periods with different tidal strain amplitudes. The seismic velocity changes decrease and increase during dilatation and contraction periods, respectively, when analyzing the cross‐correlations functions at early lapse times ranging from 2 to 7 s. The strain sensitivity of seismic velocity changes is estimated to be − 2 . 1 ± 0 . 2 × 1 0 4 at the early lapse times. However, we find that strain sensitivity of the seismic velocity changes decreases when analyzing the cross‐correlation functions at later lapse times from 7 s to 35 s. Applying an array analysis to the cross‐correlation functions, we observe apparent velocities of about 1 km/s at the early lapse times and those of higher than 1 km/s at the late lapse times. Since the group velocity of Rayleigh waves is 1.1 km/s at Izu‐Oshima volcano, the apparent velocities at the late lapse times may indicate the scattered or reflected body waves incident from a deeper region. Decrease of strain sensitivity with the lapse times therefore results from the emergence of body waves on the late lapse times. These results highlight the need to pay attention to wave types of cross‐correlation functions and their paths to interpret seismic velocity changes. Key Points: Seismic velocity decreases and increases during dilatation and contraction periods, respectively, at lapse times from 2 to 7 s Array analysis enables us to understand wave properties of cross‐correlations functions accurately Strain sensitivity of seismic velocity changes decreases with lapse times because scattered body waves contaminate the cross‐correlation functions